Impact of Macrolide Antibiotics on Hospital Readmissions and other Clinically Important Outcomes in Critically Ill Patients with Acute Exacerbations of Chronic Obstructive Pulmonary Disease: A Propensity Score–Matched Cohort Study - Kiser, Tyree H. (Pharmacotherapy, 2019)
STUDY OBJECTIVE: To assess whether a macrolide-based antibiotic treatment strategy reduces in-hospital mortality, decreases hospital readmissions, or improves other clinically important outcomes compared with a non-macrolide antibiotic treatment strategy in critically ill patients with acute exacerbations of chronic obstructive pulmonary disease (AECOPD). DESIGN: Propensity score–matched pharmacoepidemiologic cohort study. DATA SOURCE: Premier’s Perspective Hospital Database. PATIENTS: A total of 28,700 adults aged 40 years or older who were admitted to one of 566 United States intensive care units and had the primary diagnosis of AECOPD between January 2010 and December 2014, and received antibiotic treatment within 2 days of hospital admission were included. Patients were divided into macrolide (11,602 patients [40%]) or non-macrolide (17,098 patients [60%]) antibiotic treatment groups. Propensity score analysis successfully matched 8,660 patients in each treatment group. MEASUREMENTS AND MAIN RESULTS: In the matched cohort, the macrolide treatment group was not associated with decreased hospital mortality after day 2 (3.0% vs 3.3%, p=0.28), intensive care unit length of stay (2 days vs 2 days, p=0.12), hospital length of stay (6 days vs 6 days, p=0.86), or length of assisted ventilation (3 days vs 3 days, p=0.71), compared with the non-macrolide treatment group. However, a macrolide-based antibiotic regimen was associated with an overall reduction in 30-day hospital readmissions (7.3% vs 8.8%, p<0.01), increased time to next all-cause (159 vs 130 days, p<0.01) or AECOPD (200 vs 175 days, p=0.03) readmission, and decreased hospital costs ($32,730 vs $34,021, p<0.01). CONCLUSION: The results of this study suggest that inclusion of a macrolide antibiotic in the treatment regimen may have both acute and sustained benefits in critically ill patients admitted to the intensive care unit with an AECOPD, including reductions in hospital readmissions and improvements in time to next readmission.